2010
DOI: 10.1111/j.1365-2966.2010.16970.x
|View full text |Cite
|
Sign up to set email alerts
|

Double and single recycled pulsars: an evolutionary puzzle?

Abstract: We investigate the statistics of isolated recycled pulsars and double neutron star binaries in the Galactic disk. Since recycled pulsars are believed to form through accretion and spinup in close binaries, the isolated objects presumably originate from disrupted progenitors of double neutron stars. There are a comparable number of double neutron star systems compared to isolated recycled pulsars. We find that standard evolutionary models cannot explain this fact, predicting several times the number of isolated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 83 publications
(140 reference statements)
4
54
0
Order By: Relevance
“…Other authors sometimes use a Maxwellian distribution with a similar average (e.g., following Hobbs et al 2005) but it can readily be understood that both treatments yield very similar results. Some recent results however point to lower velocities (e.g., Belczynski et al 2010b). To test the influence on our results, a calculation is presented with an average kick velocity of 265 km s −1 .…”
Section: Massive Close Binary Evolutionmentioning
confidence: 83%
“…Other authors sometimes use a Maxwellian distribution with a similar average (e.g., following Hobbs et al 2005) but it can readily be understood that both treatments yield very similar results. Some recent results however point to lower velocities (e.g., Belczynski et al 2010b). To test the influence on our results, a calculation is presented with an average kick velocity of 265 km s −1 .…”
Section: Massive Close Binary Evolutionmentioning
confidence: 83%
“…But this initial NS mass can be larger by as much as 0.1 M e . In many cases, the first neutron star formed also goes through a common envelope phase where it can accrete up to ∼0.1 M e through hypercritical accretion (Fryer et al 1996;Belczynski et al , 2010bMacleod & Ramirez-Ruiz 2015a, 2015b.…”
Section: Tying It All Together: Population Synthesismentioning
confidence: 99%
“…For example, the value of σ kick is expected to be in excess of ∼100−200 km s −1 based on measurements of proper motions for isolated radio pulsars (Lyne & Lorimer 1994;Hansen & Phinney 1997;Cordes & Chernoff 1998;Arzoumanian et al 2002;Hobbs et al 2005), but is expected to be smaller based on recent observation of NSs found in binaries (on the order of 100 km s −1 , Pfahl et al 2002;Belczynski et al 2010b;Wong et al 2010;Bodaghee et al 2012) and BPS simulations (on the order of ∼150 km s −1 , Zuo et al 2014;Belczynski et al 2010b). I adopt σ kick = 150 km s −1 in the basic model (model BAC, see Table 1).…”
Section: Assumptions and Input Parametersmentioning
confidence: 99%
“…By comparing the predictions with the observed properties of sources interested, the natal kick can be properly constrained. Such works have been carried out extensively by several authors, such as Deway & Cordes (1987), Fryer & Kalogera (1997a,b), Fryer et al (1998), Belczynski et al (2010b) on single pulsars and/or double NS binaries, and Repetto et al (2012) on BH XRBs. For example, recently, Repetto et al (2012), by comparing the synthesized BH low-mass X-ray binary (LMXB) population with the Galactic distribution, concluded that BHs are most likely to have the same/similar distribution of kick velocities as NSs.…”
Section: Introductionmentioning
confidence: 99%